Rapid Prototyping of Carbon‐Bonded Alumina Filters with Flame‐Sprayed Alumina Coating for Bottom‐Teeming Steel Ingot Casting. Issue 2 (19th August 2021) - Wetzig, Tony; Neumann, Marc; Schwarz, Matthias; Schöttler, Leandro; Abendroth, Martin; Aneziris, Christos G.
Abstract : Although continuous casting is the state‐of‐the‐art casting method in steelmaking, ingot casting by bottom teeming has kept its relevance, for example, in the area of specialty steels. The main challenge is to meet the ever‐increasing quality requirements demanded by the customers. Regarding high‐performance steel applications, the purity with respect to the content of nonmetallic inclusions thereby is of special interest. Herein, foam templates with tailored geometry are designed and manufactured by selective laser sintering. Different coating techniques based on carbon‐bonded alumina slurries are applied to replicate foam structures with miniature cube geometry and cylindrical geometry. The techniques are evaluated regarding the porosity, pore size distribution, bulk density, mechanical strength, and shrinkage of the resulting filters. Suitable processing routes are selected to manufacture prototype batches with near‐net‐shape geometry. Finally, the feasibility of applying a flame spray coating is tested. First samples of the prototype batch are tested in industrial bottom‐teeming ingot casting. Abstract : A rapid prototyping approach for the manufacturing of filters for the steel melt filtration in bottom‐teeming ingot casting is investigated. Polyurethane templates with tailored geometry are manufactured additively via selective laser sintering and replicated using distinct slurry coating techniques based on carbon‐bonded alumina. Final carbon‐bonded prototypes are coated with alumina flame spraying and tested in industrial ingot casting.